2009
DOI: 10.1214/08-aop446
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of edge-reinforced random walk on a two-dimensional graph

Abstract: We consider a linearly edge-reinforced random walk on a class of two-dimensional graphs with constant initial weights. The graphs are obtained from $\mathbb{Z}^2$ by replacing every edge by a sufficiently large, but fixed number of edges in series. We prove that the linearly edge-reinforced random walk on these graphs is recurrent. Furthermore, we derive bounds for the probability that the edge-reinforced random walk hits the boundary of a large box before returning to its starting point.Comment: Published in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 10 publications
2
46
0
Order By: Relevance
“…Finally, we can deduce recurrence of the ERRW in dimension 2 from Theorem 1, Proposition 5 and the estimates obtained by Merkl and Rolles in [15,17] 1 .…”
Section: Nb: the Action Ofmentioning
confidence: 59%
See 2 more Smart Citations
“…Finally, we can deduce recurrence of the ERRW in dimension 2 from Theorem 1, Proposition 5 and the estimates obtained by Merkl and Rolles in [15,17] 1 .…”
Section: Nb: the Action Ofmentioning
confidence: 59%
“…e.g. [1,8,17,20]. In particular, in was proved in 2012 by Sabot, Tarrès, [20], and Angel, Crawford, Kozma, [1], on any graph with bounded degree at strong reinforcement (i.e.…”
Section: Consequences For the Edge Reinforced Random Walk (Errw) Thementioning
confidence: 93%
See 1 more Smart Citation
“…See [1] for a discussion and precise statements. It has also been shown that the linearly edge-reinforced random walk (ERRW) with constant initial weights is recurrent in two dimensions [19,24], but the recurrence of the VRJP for all initial rates was an open problem until the present work. The relation between the ERRW and VRJP is discussed below.…”
Section: Introduction and Resultsmentioning
confidence: 93%
“…for all β > 0 in the case of H 2 and for all sufficiently large β > 0 for H 2|2 . In the H 2|2 case (19) corresponds to transience of the VRJP (in the sense of bounded expected local time, see Corollary 1.10 below) and to the uniform boundedness (in the spectral parameter z ∈ C + ) of the expected square of the absolute value of the resolvent for random band matrices in the sigma model approximation [27] (recall Section 1.1). It also implies that the hyperbolic symmetry is spontaneously broken.…”
Section: Hyperbolic Mermin-wagner Theoremmentioning
confidence: 99%